Perkembangan Historiografi Indonesia - Ahmad Nurhuda; Anggeni Syaputri (Tarikhuna: Journal of History and History Education, 2022)
The development of historiography in Indonesia cannot be separated from the historical background of the Indonesian nation. In the development of historical writing in Indonesia, several patterns or patterns of historiography stand out, namely, traditional historiography, colonial historiography and finally, national historiography or modern historiography. Each of these historiography certainly has its own characteristics. Like traditional historiography which is still thick with elements of myth and existed before the colonial period, even traditional historiography existed during the royal period. After that, traditional historiography changed to colonial historiography due to the entry of colonialists into this country. Colonial histiriography was also written by historians or people from the colonial government, the essence of which was that it was westerners who made it. Then after Indonesia was able to defeat the invaders, it changed to national historiography. The author is an Indonesian historian, and in writing, he genuinely knows Indonesia. Keywords: Historiograf, Indonesia, Tradisional, Kolonial, Moder.